Nasal continuous positive airway pressure with head cap fixation as a contributing factor to extensive scalp necrosis in a preterm neonate with early-onset sepsis and scalp hematoma - P. Zachhau; A. E. Gravergaard; H. T. Christesen (BMC, 2019)
Abstract Background Nasal continuous positive airway pressure (CPAP) is widely used in the treatment and prevention of respiratory distress in preterm neonates, with only few severe adverse skin effects reported. Case presentation A preterm neonate was born at 34 + 1 weeks of gestation, birth weight 1860 g, and presented with early-onset sepsis (EOS) and scalp hematoma. He developed respiratory distress day 2 after birth. Antibiotics, nasal CPAP and other supportive treatment were initiated. A scalp hematoma in the occipital region was complicated by nasal CPAP cap pressure leading to an extensive scalp necrosis equaling 6% of the total body surface. Debridement and skin grafting were performed day 11, and 51, respectively. The boy survived with good healing of the skin graft. Conclusion The nasal CPAP head cap contributed to the development of severe, but potentially preventable, scalp necrosis in a preterm with birth-related scalp skin injury and EOS.